2020
DOI: 10.3389/fpls.2020.600820
|View full text |Cite
|
Sign up to set email alerts
|

Rice OsBRCA2 Is Required for DNA Double-Strand Break Repair in Meiotic Cells

Abstract: The mammalian BREAST CANCER 2 ( BRCA2 ) gene is a tumor suppressor that plays a crucial role in DNA repair and homologous recombination (HR). Here, we report the identification and characterization of OsBRCA2 , the rice orthologue of human BRCA2 . Osbrca2 mutant plants exhibit normal vegetative growth but experience complete male and female sterility as a consequence of severe meiotic defects. Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
(120 reference statements)
1
10
0
Order By: Relevance
“…Kumar reported that BRCA2 is a positive accelerator that provides the stabilizing functions and FIGL1 acts as a negative regulator to disassemble the filaments in Arabidopsis [ 41 ]. Fu also confirmed that OsBRCA2 is indispensable for facilitating the loading of OsRAD51 and OsDMC1 onto 3′ ssDNA of programmed DSBs during meiosis to facilitate single-end invasions of homologous chromosomes and precise recombination in rice [ 65 ]. Our data suggest that other proteins may mediate the functions of these two recombinases during rice meiosis.…”
Section: Discussionmentioning
confidence: 93%
“…Kumar reported that BRCA2 is a positive accelerator that provides the stabilizing functions and FIGL1 acts as a negative regulator to disassemble the filaments in Arabidopsis [ 41 ]. Fu also confirmed that OsBRCA2 is indispensable for facilitating the loading of OsRAD51 and OsDMC1 onto 3′ ssDNA of programmed DSBs during meiosis to facilitate single-end invasions of homologous chromosomes and precise recombination in rice [ 65 ]. Our data suggest that other proteins may mediate the functions of these two recombinases during rice meiosis.…”
Section: Discussionmentioning
confidence: 93%
“…Arabidopsis and rice brca2 mutants however show hypersensitivity to genotoxic agents suggesting repairing DNA damage and genomic instability Fu et al, 2020). Similar to their human homologs, both Arabidopsis and rice BRCA2 proteins interact with RAD51 and DMC1 (Siaud et al, 2004;Dray et al, 2006;Fu et al, 2020). During meiosis, Arabidopsis and rice mutants display a lack of RAD51 and DMC1 foci, incomplete synapsis, and chromosome fragmentation suggesting unrepair breaks (Fig.…”
Section: Brca2mentioning
confidence: 93%
“…Unlike the lethality caused by disruption of the BRCA2 gene in mammals that prevented genetic analysis, plant brca2 mutants are viable and grow without developmental defects. Arabidopsis and rice brca2 mutants however show hypersensitivity to genotoxic agents suggesting repairing DNA damage and genomic instability Fu et al, 2020). Similar to their human homologs, both Arabidopsis and rice BRCA2 proteins interact with RAD51 and DMC1 (Siaud et al, 2004;Dray et al, 2006;Fu et al, 2020).…”
Section: Brca2mentioning
confidence: 99%
“…RAD51C and XRCC3 facilitate the RAD51 chromosome localization ( Su et al, 2017 ; Jing et al, 2019 ; Zhang et al, 2020c ). RAD51 and DMC1 also associate with other proteins modulating their activities such as BRCA2 ( Siaud et al, 2004 ; Dray et al, 2006 ; Seeliger et al, 2012 ; Fu et al, 2020 ), FIGL1 and FLIP ( Zhang P. et al, 2017 ; Fernandes et al, 2018a ; Kumar et al, 2019 ), or MND1, and HOP2 ( Vignard et al, 2007 ; Uanschou et al, 2013 ; Aklilu et al, 2020 ). Rice MND1/MSF1 can interact with RPA2b and HOP2 ( Lu et al, 2020 ), while OsHOP2 can directly interact with the SC central element ZEP1/ZYP1 suggesting a second mechanism for the link observed between early recombination and synapsis ( Shi et al, 2019 ) at the SEI step.…”
Section: Single-end Invasions and Pairingmentioning
confidence: 99%